Tetrahydrofuran and preparation method thereof
By using a supported catalyst composed of high-strength molybdenum disulfide/porous carbon support and nickel and hydrophobic compounds, the problems of decreasing catalyst activity and high impurity content in tetrahydrofuran synthesis are solved, and a long-term production of high-purity tetrahydrofuran is achieved.
Patent Information
- Application Number
- CN202411658132.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing tetrahydrofuran synthesis methods have problems such as decreasing catalyst activity, equipment corrosion, high impurity content and high separation cost, making it difficult to ensure long-term production and high-purity products.
A high-strength molybdenum disulfide/porous carbon support is used to combine nickel and hydrophobic compounds to form a supported catalyst to avoid catalyst loss, and to control the degree of hydrogenation by adjusting the reaction conditions to ensure product purity.
The production of tetrahydrofuran is achieved with high purity (≥99.990%), avoiding the problems of decreasing catalyst activity and high impurity content, ensuring the stability of long-term production and the acquisition of high-purity products.
Smart Images

Figure CN119504662A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of synthesis technology, and particularly relates to tetrahydrofuran and a preparation method thereof. Background Art
[0002] Tetrahydrofuran (THF) is a heterocyclic organic compound with good chemical stability and solubility. It is an important organic and fine chemical raw material and is widely used in various organic reactions and polymerization reactions, especially in the fields of medicine, chemical industry and daily chemical industry.
[0003] At present, the methods for synthesizing tetrahydrofuran mainly include the furfural method, the 1,4-butanediol dehydration method and the maleic anhydride hydrogenation method. The furfural method is to separate furan from the decarbonylation reaction of furfural, and then separate and purify it by hydrogenation to prepare tetrahydrofuran, but its process is relatively complicated. The 1,4-butanediol dehydration method is to dehydrate 1,4-butanediol into a ring under acidic or alkaline catalyst conditions, and then separate it to obtain tetrahydrofuran. This scheme is the most common method for producing tetrahydrofuran in industry. The method has a simple process and high yield. This method usually uses highly acidic concentrated sulfuric acid and phosphoric acid as catalysts, which causes equipment corrosion. In addition, since 1,4-butanediol contains methyl butanediol, the tetrahydrofuran will contain methyl tetrahydrofuran impurities after dehydration, and the separation cost is relatively high. The maleic anhydride hydrogenation method is to hydrogenate maleic anhydride and its derivatives to prepare a mixture of succinic anhydride, tetrahydrofuran, γ-butyrolactone and 1,4-butanediol, and then separate and distill to prepare tetrahydrofuran. The characteristic of this technology is that it can produce succinic anhydride, tetrahydrofuran, γ-butyrolactone and 1,4-butanediol at the same time according to different process conditions. The main disadvantages are that there are many hydrogenation by-products and high separation costs. In addition, the maleic anhydride hydrogenation acidic reaction system is generally not acid-resistant, which will lead to poisoning of the active center and cannot be produced for a long period of time.
[0004] Therefore, the directional and highly selective hydrogenation of maleic anhydride is a new process for preparing methyltetrahydrofuran-free and high-purity tetrahydrofuran, which has great industrial production value. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides tetrahydrofuran and a preparation method thereof. The high-strength molybdenum disulfide / porous carbon carrier is used to avoid the problem that the non-precious metal nickel and copper catalytic centers are lost to the product under pressurized hydrogenation conditions, thereby causing the catalyst activity to gradually decrease, thereby ensuring long-term production. In addition, the hydrophobic compound can make the hydrogenation product quickly desorb from the catalyst surface, and the degree of hydrogenation of maleic anhydride C=C and its two C=O bonds can be adjusted by adjusting the reaction pressure and temperature to obtain the target product.
[0006] The first object of the present invention is to provide tetrahydrofuran, wherein the purity of the tetrahydrofuran is ≥99.990%, the tetrahydrofuran does not contain succinic anhydride and methyltetrahydrofuran, and the rest is impurities; the impurities include gamma-butyrolactone, the content of which is ≤0.009%, and 1,4-butanediol, the content of which is ≤0.004%.
[0007] The second object of the present invention is to provide a method for preparing tetrahydrofuran, wherein maleic anhydride solution and hydrogen are introduced into a reactor containing a supported catalyst for reaction, and then tetrahydrofuran is obtained by separation and purification;
[0008] The preparation method of the supported catalyst comprises the following steps:
[0009] S1, heat treating the asphalt and molybdenum disulfide to obtain a porous carbon / molybdenum disulfide carrier;
[0010] S2, dispersing the nickel precursor and the hydrophobic compound in water to obtain a mixed solution; the structural formula of the hydrophobic compound is n≥6;
[0011] S3. The porous carbon / molybdenum disulfide carrier described in S1 is immersed in the mixed solution described in S2, and the supported catalyst is obtained through aging, drying and thermal reduction treatment.
[0012] In one embodiment of the present invention, in S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5-5:1; and the molybdenum disulfide is a nano-sheet structure with 5-20 layers.
[0013] In one embodiment of the present invention, in S1, the heat treatment is performed in an oxygen atmosphere at 200° C.-400° C. for 3 h-8 h.
[0014] In one embodiment of the present invention, in S2, the nickel precursor is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate.
[0015] In one embodiment of the present invention, in S3, the aging temperature is 50℃-80℃, and the time is 12h-16h; the drying temperature is 100℃-150℃, and the time is 10h-14h; the thermal reduction treatment is in a hydrogen atmosphere, heating to 160℃-200℃ at a rate of 10℃ / h-20℃ / h, and reducing for 6h-10h.
[0016] In one embodiment of the present invention, the nickel loading in the supported catalyst is 30wt%-60wt%, the hydrophobic compound loading is 0.01wt%-0.2wt%; the pore volume of the porous carbon / molybdenum disulfide carrier is 0.2mL / g-0.7mL / g, the particle size is 3mm-5mm, and the bulk density is 750kg / m 3 -1100kg / m 3 The length of the cluster is 80nm-150nm, the width is 30nm-100nm, and the thickness is 10nm-30nm; the cluster is an active center composed of nickel, copper, and hydrophobic compounds supported on a porous carbon / molybdenum disulfide carrier.
[0017] In one embodiment of the present invention, the mass fraction of the maleic anhydride solution is 5wt%-30wt%; the solvent of the maleic anhydride solution is selected from one or more of tetrahydrofuran, γ-butyrolactone, ether, ethyl acetate, ethyl formate and methyl acetate; preferably, the solvent of the maleic anhydride solution is selected from tetrahydrofuran and / or γ-butyrolactone.
[0018] In one embodiment of the present invention, the reaction pressure is 5MPa-15MPa, the temperature is 120℃-200℃, and the air velocity is 0.6hr -1 -6.0hr -1 .
[0019] Preferably, the reaction pressure is 6MPa-10MPa, and the temperature is 130°C-180°C.
[0020] In one embodiment of the present invention, the flow rate ratio of the maleic anhydride solution and hydrogen is (0.1-5):(0.1-100).
[0021] The porous carbon / molybdenum disulfide carrier of the present invention, due to the layered structure characteristics of molybdenum disulfide, when the carrier is subjected to high temperature treatment, the asphalt will extend along the layered voids, and then undergo dehydration, deorganization and other processes at a certain temperature to form a layered carbon structure, which is firmly combined with molybdenum disulfide and produces a large number of pore structures, which is conducive to the dispersion of active metal components. At the same time, this composite carrier structure naturally has a very high mechanical strength, and it is easy to achieve a particle strength of ≥450N / cm, while the particle strength of traditional alumina is difficult to achieve this. The mechanical strength of alumina particles of commercial catalyst carriers can generally reach 100N / cm.
[0022] The technical solution of the present invention has the following advantages over the prior art:
[0023] (1) The supported catalyst of the present invention has a strength of more than 450 N / cm, and the metal is not easily lost during the reaction process, which plays a key role in the synthesis of high-purity tetrahydrofuran.
[0024] (2) The supported catalyst described in the present invention uses porous carbon / molybdenum disulfide as a carrier. The porous carbon / molybdenum disulfide carrier has a certain hydrogenation activity, which can promote the improvement of reaction activity, thereby reducing the reaction temperature, improving the reaction selectivity, and further improving the purity of the product.
[0025] (3) The supported catalyst of the present invention uses a hydrophobic compound as an additive, which can make the product tetrahydrofuran desorb from the surface of the supported catalyst as soon as possible. On the one hand, it can accelerate the reaction speed, and on the other hand, it can avoid further reaction of the product on the catalyst surface, thereby achieving the ultimate goal of achieving a product purity of more than 99.99% and containing no impurities such as methyltetrahydrofuran. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0027] In the present invention, unless otherwise explained, technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art to which the present invention belongs.
[0028] In the present invention, unless otherwise stated, the term "and / or" used in the present invention includes any and all combinations of one or more of the associated listed items.
[0029] In the present invention, unless otherwise stated, the experimental methods used in the embodiments of the present invention are conventional methods unless otherwise stated, and the materials, reagents, etc. used are all commercially available unless otherwise stated.
[0030] In the present invention, unless otherwise specified, the molybdenum disulfide used in the embodiments of the present invention is a nanosheet structure with 5-20 layers.
[0031] Example 1
[0032] The tetrahydrofuran and preparation method thereof of the present embodiment specifically comprise the following steps:
[0033] S1. Preparation of supported catalyst
[0034] S11. Preparation of porous carbon / molybdenum disulfide carrier: Asphalt and molybdenum disulfide were stirred and mixed in a mass ratio of 1:1, and heat treated at 300°C for 4 h under oxygen conditions to obtain a pore volume of 0.5 mL / g, a particle size of 5 mm, and a bulk density of 850 kg / m 3 A porous carbon / molybdenum disulfide support;
[0035] S12, preparation of a mixed solution: weigh 50.00 g of basic nickel carbonate, 159.5 mL of a 5 mol / L dilute nitric acid solution, 0.30 g of sodium dodecyl sulfate and 500.00 g of deionized water, and stir at 45° C. until all solids are dissolved to obtain a mixed solution;
[0036] S13, preparation of supported catalyst: the porous carbon / molybdenum disulfide support was immersed in the mixed solution, aged at 60°C for 14h under stirring, then dried at 120°C for 12h, finally loaded into tube arrays, heated to 200°C at a heating rate of 20°C / h under hydrogen conditions and reduced for 6h, to obtain a supported catalyst with a cluster length of about 125nm, a width of about 67nm, and a thickness of about 27nm;
[0037] S2. Preparation of tetrahydrofuran
[0038] S21, preparation of maleic anhydride solution: dissolving maleic anhydride in tetrahydrofuran to obtain a maleic anhydride solution with a mass fraction of 5 wt%;
[0039] S22. Preparation of tetrahydrofuran: Maleic anhydride solution and hydrogen were mixed at flow rates of 0.5 mL / min and 200 mL / min respectively and then continuously introduced into a 50 mL hydrogenation tubular reactor filled with a supported catalyst for reaction at a reaction temperature of 145°C, a reaction pressure of 6.8 MPa(A), and a space velocity of 0.6 hr -1 , and then continuously enters the distillation separation tower for separation and purification to obtain the product.
[0040] Example 2
[0041] The process is basically the same as Example 1, except that during the preparation of the supported catalyst, basic nickel carbonate is replaced by nickel nitrate.
[0042] Example 3
[0043] The method is basically the same as Example 1, except that during the preparation of tetrahydrofuran, the 5 wt % maleic anhydride solution is replaced by a 10 wt % maleic anhydride solution.
[0044] Example 4
[0045] The method is basically the same as Example 1, except that in the preparation process of tetrahydrofuran, the solvent tetrahydrofuran of the maleic anhydride solution is replaced by the solvent γ-butyrolactone.
[0046] Comparative Example 1
[0047] The method is basically the same as Example 1, except that sodium dodecyl sulfate is not added during the preparation of the supported catalyst.
[0048] Comparative Example 2
[0049] The method is basically the same as Example 1, except that molybdenum disulfide is not added during the preparation of the supported catalyst.
[0050] Test Example 1
[0051] The strength test of the supported catalysts of Examples 1-4 and Comparative Example 2 was carried out according to the HG / T 2782 standard. The results are shown in Table 1:
[0052] Table 1
[0053] Sample Strength (N / cm) Example 1 453.8 Example 2 455.2 Example 3 453.8 Example 4 453.8 Comparative Example 2 200.2
[0054] It can be seen from Table 1 that the strength of the supported catalyst prepared in the example exceeds 450 N / cm. By combining high-strength molybdenum disulfide with porous carbon, the strength of the supported catalyst can be greatly improved.
[0055] Test Example 2
[0056] The product purity and impurity content of Examples 1-4 and Comparative Examples 1-2 were tested by gas chromatography, using a gas chromatography column HP-5 (30m×320μm×0.25μm) and an FID detector; the column temperature conditions were an initial temperature of 60°C, a first-order termination temperature of 90°C, a heating rate of 15°C / min, and a hold time of 2min. The second-order termination temperature was 230°C, a heating rate of 10°C / min, an injection port temperature of 260°C, a split ratio of 100:1, an injection volume of 0.2μL, a hydrogen flow rate of 30mL / min, and a nitrogen flow rate of 25mL / min. Using acetone as the solvent, standard curves of maleic anhydride, succinic anhydride, methyltetrahydrofuran, tetrahydrofuran, γ-butyrolactone, and 1,4-butanediol were established. The results of the maleic anhydride conversion rate (%) and tetrahydrofuran selectivity (%) during the continuous experiment of the hydrogenation process for 1000h are shown in Table 2:
[0057] Table 2
[0058]
[0059]
[0060] As can be seen from Table 2, the method of the present invention can prepare high-purity tetrahydrofuran.
[0061] Obviously, the above embodiments are only examples for clear explanation and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
Claims
1. A tetrahydrofuran, characterized in that The tetrahydrofuran has a purity of ≥99.990%, does not contain succinic anhydride and methyltetrahydrofuran, and the rest are impurities; the impurities include gamma-butyrolactone with a content of ≤0.009% and 1,4-butanediol with a content of ≤0.004%.
2. A method for preparing tetrahydrofuran as claimed in claim 1, characterized in that: A maleic anhydride solution and hydrogen are introduced into a reactor containing a supported catalyst to react, and then tetrahydrofuran is obtained through separation and purification; The preparation method of the supported catalyst comprises the following steps: S1, heat treating the asphalt and molybdenum disulfide to obtain a porous carbon / molybdenum disulfide carrier; S2, dispersing the nickel precursor and the hydrophobic compound in water to obtain a mixed solution; the structural formula of the hydrophobic compound is n≥6; S3. The porous carbon / molybdenum disulfide carrier described in S1 is immersed in the mixed solution described in S2, and the supported catalyst is obtained through aging, drying and thermal reduction treatment.
3. The preparation method of tetrahydrofuran (THF) according to claim 2, wherein In S1, the mass ratio of the asphalt to molybdenum disulfide is 1:5-5:1; and the molybdenum disulfide is a nano-sheet structure with 5-20 layers.
4. The method for preparing tetrahydrofuran (THF) according to claim 2, wherein In S1, the heat treatment is performed in an oxygen atmosphere at 200°C-400°C for 3h-8h.
5. The method for preparing tetrahydrofuran according to claim 1, characterized in that, In S2, the nickel precursor is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, basic nickel carbonate, nickel acetylacetonate, nickel oxalate, nickel acetate, nickel citrate, nickel hypophosphite, nickel phosphate and nickel formate.
6. The method for preparing tetrahydrofuran according to claim 2, characterized in that, In S3, the aging temperature is 50℃-80℃, and the time is 12h-16h; the drying temperature is 100℃-150℃, and the time is 10h-14h; the thermal reduction treatment is carried out in a hydrogen atmosphere, with the temperature being increased to 160℃-200℃ at a rate of 10℃ / h-20℃ / h, and the reduction is carried out for 6h-10h.
7. The method for preparing tetrahydrofuran according to claim 2, characterized in that, The nickel loading in the supported catalyst is 30wt%-60wt%, the hydrophobic compound loading is 0.01wt%-0.2wt%; the pore volume of the porous carbon / molybdenum disulfide carrier is 0.2mL / g-0.7mL / g, the particle size is 3mm-5mm, and the bulk density is 750kg / m 3 -1100kg / m 3 ; The length of the cluster is 80nm-150nm, the width is 30nm-100nm, and the thickness is 10nm-30nm.
8. The method for preparing tetrahydrofuran according to claim 2, characterized in that, The mass fraction of the maleic anhydride solution is 5wt%-30wt%; the solvent of the maleic anhydride solution is selected from one or more of tetrahydrofuran, γ-butyrolactone, ether, ethyl acetate, ethyl formate and methyl acetate.
9. The method for preparing tetrahydrofuran according to claim 2, characterized in that, The reaction pressure is 5MPa-15MPa, the temperature is 120℃-200℃, and the space velocity is 0.6hr -1 -6.0hr -1 .
10. The method for preparing tetrahydrofuran according to claim 2, characterized in that: The flow rate ratio of the maleic anhydride solution and hydrogen is (0.1-5):(0.1-100).
Citation Information
Patent Citations
Method for producing tetrahydrofuran
CN1485322A
improved process for the catalytic hydrogenation of maleic anhydride and catalyst therefor
FR1519062A
Hydrogenation of maleic anhydride to tetrahydrofuran
US4810807A